School-Based Mental Health Therapy : Meeting the Needs of Rural Adolescents - Mendoza, Albee Therese Ongsuco (East Carolina University, 2014)
School-based mental health (SBMH) therapy offers promise in addressing the mental health needs of rural adolescents. The current investigation includes two studies that examine rural adolescents' educational and mental health outcomes after receiving mental health services. Results from the first study which focused on educational outcomes, demonstrated no statistically significant relationship between the number of SBMH therapy sessions and the number of absences, or between the number of SBMH therapy sessions and the number of discipline referrals. Results from the second study which focused on mental health outcomes, demonstrated no statistically significant differences between pre and post treatment scores on the Youth Version of the Strengths and Difficulties Questionnaire (SDQ-Y). However, a strong, negative correlation between the number of SBMH therapy sessions and scores on the SDQ-Y Impact scale was found. Additionally, participants who only completed their pretest had lower scores on the SDQ-Y Peer Problem scale than participants who completed both pre and posttests. This investigation can inform ongoing efforts of SBMH therapy and provide recommendations for future research in the accountability, availability, accessibility, and acceptability of these services for rural adolescents.
Keywords: Psychology; Accountability; Adolescents; Rural mental health; School-based mental health; Strengths and difficulties questionnaire; University-school partnership; Rural teenagers--Mental health--North Carolina; School mental health services--North Carolina